1997
DOI: 10.1159/000177367
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Echocardiographic Findings in HIV Patients with Pericardial Effusion

Abstract: Background and Objectives: Pericardial effusion (PE) is frequently found in patients infected with the human immunodeficiency virus (HIV), but its clinical significance remains unclear. Our purpose was to study the manifestations of HIV-infected patients with PE and the coexistence of these manifestations with other echocardiographic abnormalities, compared with patients without PE. Methods: We reviewed 141 HIV-infected patients in whom echocardiographic study was performed. We studied their epidemiological, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 13 publications
1
7
0
1
Order By: Relevance
“…Therefore the mean CD4 count of cases was much less in this study as compared to other studies. 17,18 Pericardial effusion was seen in 15.53% of cases which is as par with Indian studies done by Aggarwal et al and studies done at United States by Himelman et al 14,19 The pericardial effusion detected was often small in amount and without any hemodynamic significance. Pericardial effusion in HIV patients may be marker of end stage HIV infection because it is associated with very low CD4 count.…”
Section: Resultssupporting
confidence: 50%
“…Therefore the mean CD4 count of cases was much less in this study as compared to other studies. 17,18 Pericardial effusion was seen in 15.53% of cases which is as par with Indian studies done by Aggarwal et al and studies done at United States by Himelman et al 14,19 The pericardial effusion detected was often small in amount and without any hemodynamic significance. Pericardial effusion in HIV patients may be marker of end stage HIV infection because it is associated with very low CD4 count.…”
Section: Resultssupporting
confidence: 50%
“…In contrast Moreno et al found that pericardial effusions were associated with advanced stages of the disease. 12 The association might have been obscured in our study by the relatively smaller sample. Of considerable clinical significance is the fact most pericardial effusions in our series were not clinically suspected.…”
Section: Cardiovascular Manifestations Of Hiv Infection Have Not Attrmentioning
confidence: 59%
“…HIV infection has been shown to be associated with endocardial, myocardial, and pericardial abnormalities. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] HIV associated myocarditis has been extensively studied with HIV virions detected in myocardial cells of HIV infected patients. 8 Many studies have shown that HIV is an important cause of dilated cardiomyopathy.…”
mentioning
confidence: 99%
“…[18] Reduction in ejection fraction without global hypokinesia or chamber enlargement but without any symptom probably represented a mild form of cardiac disease that will progress to a clinically evident form of dilated cardiomyopathy. [7] Dilated cardiomyopathy was seen in 9.25% of the cases whereas studies published by Moreno et al [19] and Hakim et al [20] had detected 6% and 5% respectively. Pulmonary artery hypertension was noted in 6 cases (11.1%) which was higher than normal population and comparable to studies done by Pellicelli et al [21] and Mehta et al [22] who also found higher incidence of pulmonary artery hypertension in HIV patients than normal population.…”
Section: Discussionmentioning
confidence: 91%